Peningkatan Penguasaan Kosakata Bahasa Arab melalui Micromodule Digital Berbasis Heyzine Flipbook di SMP Muhammadiyah 5 Mariso - Nursamsi; Syamsu Rijal; Fauziah Bacthiar (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
This research is a Classroom Action Research (CAR) conducted in two cycles. This research aims to address the low mastery of Arabic vocabulary of eighth-grade students of SMP Muhammadiyah 5 Mariso through the implementation of a digital micromodule based on Heyzine Flipbook. The subjects of this research were all 15 eighth-grade students with a purposive sampling technique. Data analysis techniques used qualitative and quantitative. Based on the results of the analysis, it was found that the conditions of cycle I successfully improved compared to the pre-cycle conditions with an average of 84.61 and a completion percentage of 70%. Because it had not met the 75% success criteria, the action continued to Cycle II. This Cycle II focused on qualitative improvements, namely improving classroom management by researchers to address discipline problems and lack of student concentration detected in Cycle I as well as checking the availability of teaching materials. This corrective action was completely successful, resulting in a significant increase with an average of 91.15 and a completion percentage of 92%, exceeding the set target.  Qualitatively, students responded positively to the micromodule media because its interactive and audio-visual format (especially the songs) was considered fun and exciting, which effectively increased motivation and facilitated vocabulary recall. Thus, it can be concluded that the implementation of the Heyzine Flipbook-based digital micromodule was proven to be successful and comprehensive in improving students' Arabic vocabulary mastery.